CLASSIC AND MODERN TECHNOLOGIES FOR THE DESIGN AND PROCESSING OF A PART WITH MEDIUM DIAMETERS BASED ON MEASUREMENTS IN 3D COORDINATES - Elena Stela Muncut; Mihail Aurel Titu; Lavinia Ioana Culda; Geza Mihai Erdodi (Nonconventional Technologies Review)
The present paper presents a parallel between the classic and modern technologies used to obtain a part with medium diameters. The part for which this case study is done is a planetary end. To obtain the benchmark, the following is used: the CTXBeta1250 4A machining centre, which is a turning centre with two main-motor shafts (main and secondary) ISM 76, with a power of 25/32 KW (33.5/42.88hp) (100/40%d.c.). The machining procedure is designed for both classic cutting machines and CNCs. The measurement is performed on the Mitutoyo 9106 measuring machine according to the measurement procedure and will allow the recording of: limit deviation, limit size, control limits and means of measurement. All the technological flow presented is based on quality assurance and all operations are accompanied by a procedure that ensures the traceability of the entire process of making the part.